2016
DOI: 10.1007/jhep04(2016)187
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on leptoquark models from IceCube data

Abstract: Leptoquarks in the mass range of 500-1000 GeV can be resonantly produced in significant numbers by PeV neutrino interacting with nuclei at IceCube. We compute the event rates of leptoquark production and decay events and use the 3-year IceCube data for PeV energy events to find the allowed range of the leptoquarks mass and coupling parameter space. We use a low-scale quark lepton unification model based on the SU(4) C ⊗ SU(2) L ⊗ U(1) R gauge group where leptoquark couplings which give rise to proton decay are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Predictably, a lot of excitement have been generated by this momentous discovery [3][4][5][6][7][8][9][10][11]. Together with the prior discovery of a diffuse flux of high-energy astrophysical neutrinos [12,13], these observations provide us a new way to probe beyond the Standard model physics [14][15][16][17][18][19][20][21][22], new IceCube signal morphologies [23,24], and atmospheric prompt neutrinos [25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Predictably, a lot of excitement have been generated by this momentous discovery [3][4][5][6][7][8][9][10][11]. Together with the prior discovery of a diffuse flux of high-energy astrophysical neutrinos [12,13], these observations provide us a new way to probe beyond the Standard model physics [14][15][16][17][18][19][20][21][22], new IceCube signal morphologies [23,24], and atmospheric prompt neutrinos [25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Even without SUSY, similar resonance features in neutrino-nucleon interactions can also occur in models with TeV-scale leptoquarks[95][96][97][98][99][100][101][102][103]. However, there are subtle differences between scalar leptoquark and RPV SUSY models, e.g.…”
mentioning
confidence: 90%
“…This distinction is important, as the different contributions to the event rates have very different topological signatures. These are crucial: previous studies [50,52,53,56,57] have examined the impact of an extra leptoquark-induced interaction (or a similar R-parity violating SUSY model [54]) on the best-fit fluxes reported by the IceCube Collaboration. However, this is not self-consistent, as the fluxes were derived using the same data set.…”
Section: B Comparison With Icecube Datamentioning
confidence: 99%
“…Indeed, the center of mass energy scale of a PeV neutrino colliding with a nucleon at rest is just the right scale to excite a ∼TeV leptoquark resonance [65]. Many studies have made the claim that such a process can improve the fit to the observed event rate [50,[52][53][54]56,57]. These are often framed in terms of an excess that requires a nonstandard explanation; however, it should be stressed that the observed event rate falls within the expected Waxman-Bahcall flux [66], consistent with a common origin with cosmic rays (see also [67] for a review).…”
Section: Introductionmentioning
confidence: 99%